Analysis of Non-Uniform Shrinkage Effect in Box Girder Sections for Long-Span Continuous Rigid Frame Bridge - Zhuoya Yuan; Pui-Lam Ng; Darius Bačinskas; Jinsheng Du (The Baltic Journal of Road and Bridge Engineering)
To consider the effect of non-uniform shrinkage of box girder sections on the long-term deformations of continuous rigid frame bridges, and to improve the prediction accuracy of analysis in the design phase, this paper proposes a new simulation technique for use with general-purpose finite element program. The non-uniform shrinkage effect of the box girder is transformed to an equivalent temperature gradient and then applied as external load onto the beam elements in the finite element analysis. Comparative analysis of the difference in deflections between uniform shrinkage and nonuniform shrinkage of the main girder was made for a vehicular bridge in reality using the proposed technique. The results indicate that the maximum deflection of box girder under the action of non-uniform shrinkage is much greater than that under the action of uniform shrinkage. The maximum downward deflection of the bridge girder caused by uniform shrinkage is 5.6 mm at 20 years after completion of bridge deck construction, whereas the maximum downward deflection caused by non-uniform shrinkage is 21.6 mm, which is 3.8 times larger. This study shows that the non-uniform shrinkage effect of the girder sections has a significant impact on the long-term deflection of continuous rigid frame bridge, and it can be accurately simulated by the proposed transformation technique.